12.5k views
1 vote
If you were to use the substitution method to solve the following system, choose the

new equation after the expression equivalent to x from the second equation is
substituted into the first equation.

2x-3y=-29
X+4y=13

If you were to use the substitution method to solve the following system, choose the-example-1

1 Answer

13 votes

Answer:

x + 4y = 13

x = -4y + 13....now we sub this into the first equation

2x - 3y = -29

2(-4y + 13) - 3y = -29 <=====

-8y + 26 - 3y = -29

-11y + 26 = -29

-11y = -29 - 26

-11y = -55

y = 55/11

y = 5

x = -4y + 13

x = -4(5) + 13

x = -20 + 13

x = -7

Explanation:

User Ray Zhang
by
5.0k points